Pelatihan Program Pengembangan Keprofesian Berkelanjutan (PKB) Untuk Guru Sekolah Dasar di Lingkungan Dinas Pendidikan dan Kebudayaan Kota Sukabumi - Dyah Lyesmaya; Fanny Sumirat; Deden Sumiarsa; Iis Nurasi’ah; Rohmat Widiyanto; Din Azwar Uswatun; Arif Yudiyanto; Zaenudin Aang (Universitas Mathla'ul Anwar Banten, 2017)
Becoming a teachers means always encourage yourself for longlife education. This is one of the benefit in Teacher career. We used to be learn anything and everything to update our professionalism. As a Teacher, we should be aware of teachers world, knowledge, technology, and student needs changing. Indonesian Government facilitate it through PKB (Continuity Profesionalism Development) program. PKB goals is to increasing teachers career competence continualy. Although Government publish this program since 2009, Education and Culture Departement of Sukabumi City started it in 2015 October. This lateness becoming our concern to organize a PKB Workshop specialy for elemetary school teachers. This workshop attendence by fifty teachers from seven distrik in Sukabumi city. The Workshop goals is to diseminate PKB and how to running it in teachers career. Beside that, the workshop also trained teacher how to entablish class action reasearch. This workshop held in three days from 2nd to 4th November 2016. From the workshop we know that PKB is very important to increase teachers competence and to maintain teachers career.